Determinologizacija (na primeru terminologije fizike) - Žagar, Mojca (Jezik in slovstvo, 2005)
Determinologisation describes the transition of a term from a specific terminology to a general lexical inventory, i.e. scientific discourse addressing a higly specific scientific linguistic community to a discourse aimed at the general public (frequently the language used by the mass media). Determinologisation can be divided into partial determinologisation, where the basic semantic components of the term remain unchanges, full determinologisation, where a lexeme assumes a new meaning, and individual determinologisation correlated to a creative use within a text. With the help of the SSKJ (Dictionary of the Standard Slovene language) and the FIDA reference corpus of the Slovene language, it has been tested how complete determinologisation is manifested on terms taken from the subjext of physic.
Keywords: Slovene; slovenščina; leksikologija; lexicology; terminologija; terminology; determinologizacija; fizika; physics